Mindful regulation of positive emotions: a comparison with reappraisal and expressive suppression - Lalot, Fanny; Delplanque, Sylvain; Sander, David (Frontiers in Psychology, 2014)
It is often acknowledged that mindfulness facilitates emotion regulation on a long-term scale. Only few empirical studies support the hypothesis that even a brief mindfulness induction among subjects without previous experience of meditation allows an effective reduction of both positive and negative emotions. To the best of our knowledge, this hypothesis has never been tested when comparing mindfulness to other regulation strategies known to be effective. The current study investigates the effects of mindfulness, reappraisal and expressive suppression during the regulation of positive emotions. Forty-five participants without previous meditation experience watched four positive video clips while applying a specific regulation strategy: mindful attention, reappraisal, expressive suppression or no strategy (control condition). Video clips were matched for intensity and positive emotions index. Each of them was evaluated on two dimensions, valence (negative/positive) and arousal (calming/exciting). Moreover, participants’ facial expressions were recorded during the presentation of the video clips. Results showed that (a) participants report less positive affect in reappraisal and mindful attention conditions compared to expression suppression and a control condition; and (b) the facial expression – activation of AU12 (lip corner pull) and AU6 (cheek raiser) – varies with the regulation strategy applied. Results demonstrate the effectiveness of mindfulness in decreasing both the evaluative judgment of positive video clips and the related facial expression, among participants without previous mindfulness experience.